Polyaxial polydactyly. A case report - Raquel Rojas Bruzón; Yulexis Hechavarría Jimenes; Evis Jhonson Montero; Aracelys Lores Cruz (Medisur)
Polydactyly is a congenital anomaly characterized by the existence of supernumerary or bifid fingers. This can occur isolated or associated with other malformations as part of some known syndromes. The objective of this research is to show the surgical results of two pediatric patients with a higher degree of complexity, black Africans, who presented polydactyly and were operated on by Cuban doctors in Gaborone city, Botswana. Both patients had an autosomal dominant pattern of inheritance. Surgical treatment achieved harmony and symmetry in upper and lower limbs with good aesthetic and functional results.